Brief program notes for a graduate saxophone recital: compositions by William Albright, Benjamín Gutiérrez, François Borne, and Andy Scott - Umaña Conejo, Diego (My University, 2026)
This Master’s Report presents extended program notes on four works representing diverse stylistic and historical perspectives within the alto saxophone repertoire. The pieces addressed are as follows: Three Letter Word by Andy Scott, Fantaisie Brillante sur des airs de "Carmen" by François Borne, Rapsodia for Alto Saxophone and Orchestra by Benjamín Gutiérrez, and Sonata for Alto Saxophone and Piano by William Albright. The document provides biographical background for each composer and delves into the contexts in which these compositions were created. Each chapter includes a discussion of the biography of the composer, general information about the piece, formal and stylistic design considerations, and interpretative performance considerations. The performance-related considerations addressed include technical demands, expressive challenges, phrasing, and saxophone interaction with piano. The observations are grounded in the study of the scores and supported by the practical preparation of the works for performance. This report aims to serve as a performance-oriented resource for advanced saxophonists. The goal is to support informed performance decisions and highlight the artistic and technical diversity of the modern and traditional saxophone repertoire.
Keywords: Alto saxophone; Saxophone repertoire; Program notes; Performance practice; Interpretative considerations; contemporary saxophone literature